ADAPTASI AKADEMIK OLEH SISWA DI LINGKUNGAN SEKOLAH MADRASAH ALIYAH NEGERI 2 PONTIANAK - Alpasino, Alpasino; Salim, Izhar; Al Hidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to determine academic adaptation by students in the school environment in grade X Social Science Aliyah Negeri 2 Pontianak. This study uses descriptive method with qualitative research. The data sources of this study were school students, the students of X grade Social Science are still in the process of adjustment. Data collection tools in this study used observation guides, interview guides and documentation studies. The results of this study showed that (1) the adaptation efforts undertaken by the students were conducted at the beginning of the school entry beginning with written tests, MOS activities (student orientation period) and learning activities. In terms of environmental adjustments, students were experiencing difficulties as they can not adjust in the early days. In the aspect of friendship, there are students who have students who have difficulty making friends and some who can connect their friends directly. (2) The student learning process was conducted by the students by following the learning process inside and outside the classroom. Aspects of the learning process in the classroom were carried out by students through learning activities every Monday to Saturday. Aspects of the process of classroom learning outside the classroom have been conducted by students through a series of curriculum and less activities such as drum band, limitation and English learning club activity. Keywords: Adaptation, learning process, school environment